Perbandingan Efek Samping Pemberian Ketorolac 30 mg Intravena dengan Tramadol 100 mg Intravena pada Nyeri Pasca Bedah terhadap Perubahan Kadar Hemoglobin Pasien Fraktur Shaft Femur yang Dilakukan Reduksi Terbuka dan Fiksasi Dalam di RS M. Djamil - Muhamad Ivan; Rizki Rahmadian; Nasman Puar; Rizanda Machmud (Universitas Baiturrahmah, 2021)
Introduction: Clinical manifestation of fractured femur are deformity, severe pain and sometimes shock as a result of bleeding. Thrombocytes dysfunction is one of the cause of bleeding during surgery or major injury such as fractured femur. Drug interactions that cause thrombocytes dysfunction are hazardous.5 Meanwhile, major injury like fractured femur and surgery always need analgesic. Ketorolac and tramadol become the choices in M. Djamil Hospital for analgesic therapy of fracture cases because they are the hospital formularies. Although they are from different classes, these medicine both have coagulation effect, that is interrupting thrombocytes aggregation through different channels. There are still no experiment about the effect of hemoglobin level change towards the using of those two analgesics. Aims: of this study is to know the comparison between the effect of using 30 mg ketorolac intravenous and 100 mg tramadol intravenous for post surgical pain towards hemoglobin level change of patient with shaft fracture femur who got open reduction and internal fixation treatment at M. Djamil Hospital. Method: This study used double-blind randomized clinical trial method and was held between September-December 2015. The collected data are primary data of hemoglobin levels measurement before and after the treatment given. The subjects of this study are the patients who have undergoing surgery in department of orthopedic surgery chosen based on inclusion criteria and divided into ketorolac group and tramadol group. The difference between hemoglobin level of these two groups were analyzed using independent two sample Wilcoxon-Rank test and Mann-Whitney test. Results: there is differences between hemoglobin level before and after surgery, before and after the given of analgesic in both tramadol group and ketorolac group. But, there is no significant change of hemoglobin levels after the surgery and after the given of analgesic, in both tramadol or ketorolac group. There is no difference between hemoglobin levels after the given of tramadol or ketorolac. Conclusion: there is no significant change between the average hemoglobin level after the surgery and after the given of analgesic in both tramadol and ketorolac groups. Based on statistical test, there is no difference between the hemoglobin level after the given of analgesic in both tramadol and ketorolac group.